The cross-section of currency volatility premia - Corte, Pasquale Della; Kozhan, Roman; Neuberger, Anthony (Journal of Financial Economics, 2021)
We identify a global risk factor in the cross-section of implied volatility returns in currency markets. A zero-cost strategy that buys forward volatility agreements with downward sloping implied volatility curves and sells those with upward slopes–a volatility carry strategy–generates significant excess returns. The covariation with volatility carry returns fully explains the cross-sectional variation of our slope-sorted portfolios. The lower the slope, the more the forward volatility agreement is exposed to volatility carry risk.